AB0720 Systemic sclerosis and cancer development. a single-centre experience. (12th June 2018) - Pelechas, E.; Kaltsonoudis, E.; Voulgari, P.V.; Drosos, A.A.
Abstract : Background: Systemic Sclerosis (SSc) is an autoimmune connective tissue disease with multisystem involvement, and sometimes devastating results. In bibliography there are reports that scleroderma patients present a higher incidence of risk for cancer when compared with the general population. However, different estimates have been reported. Objectives: The purpose of the present study was to evaluate the frequency of cancer development (CD) in a cohort of patients with SSc. Methods: Patients that fulfilled the 2013 American College of Rheumatology/EUropean League Against Rheumatism criteria for SSc and were followed up since 1999, were included. Date of disease onset, disease duration, autoantibodies, age, pulmonary hypertension, comorbidities and the type of CD have all been taken into account, during the period 1991–2016. Results: Seventy-nine SSc patients have been included. 46 with limited (lcSSc) and 33 with diffuse cutaneous Systemic Sclerosis (dcSSc). Six of them, (7.6%) developed different types of cancer. Most of them were adenocarcinomata. More specifically, 2 developed pulmonary adenocarcinoma (1 with lcSSc and 1 with dcSSc), 1 follicular carcinoma of the thyroid gland (lcSSc), 1 colorectal adenocarcinoma (lcSSc), 1 B-cell lymphoma (MALT lymphoma), and 1 prostate adenocarcinoma (dcSSc). Five out of six were female patients. Mean age at the time of cancer diagnosis was 66.8-years-old, while SSc has been diagnosed at the mean age of 49.4 years. Mean time of developing any type of cancer was 15.8 years after SSc diagnosis. The diagnosis of cancer was done the last 20 months. All patients were non-smokers, had gastro-oesophageal reflux disease and pulmonary fibrosis, while 4/6 had also pulmonary hypertension and were under treatment with phosphodiesterase 5 inhibitors and bosentan. Scleroderma patients with CD have been referred to the corresponding oncology clinic for further treatment. Conclusions: The present study on SSc and CDE provides data showing a potential association between the two entities. We found a high frequency of cancer development in patients with SSc (7.6%). Thus, a careful monitoring and screening is required when physicians follow-up scleroderma patients. Disclosure of Interest: None declared